Virtual reality-based music attention training for acquired brain injury: A protocol for randomized cross-over trial - Shin, Joon-Ho; Jeong, Eunju (Frontiers in Neurology, 2023)
Attention training is considered the primary step in the rehabilitation for patients with acquired brain injury (ABI). Active music performance has been reported to aid neural and functional recovery; however, its efficacy for patients with ABI remains uncertain due to methodological concerns. The purpose of the study is to develop a virtual reality-based music attention training (VR-MAT) that utilizes a visually guided, bilateral drumming in an immersive environment, targeting to train attention and executive functions. We also aims to examine the feasibility and effectiveness of the VR-MAT with a small sample size of participants (3-60 months after ABI, N= 20 approximately).Participants will be randomly assigned to either a waitlist control or music group, in which VR-MAT will take place five times weekly over four weeks (randomized crossover design). The evaluation of VR-MAT performance will include accuracy and response time in music responses. Neurocognitive outcome measures will be administered to quantify pre-post changes in attention, working memory, and executive functions. Additionally, functional near-infrared spectroscopy will be employed to explore the relationships between musical behavior, neurocognitive function, and neurophysiological responses.